Physical, cognitive and mental health outcomes in 1-year survivors of COVID-19-associated ARDS. Issue 3 (29th September 2021) - Latronico, Nicola; Peli, Elena; Calza, Stefano; Rodella, Federica; Novelli, Maria Paola; Cella, Andrea; Marshall, John; Needham, Dale M; Rasulo, Frank Antony; Piva, Simone
Abstract : We report on the outcome of 114 COVID-19-associated acute respiratory distress syndrome (ARDS) survivors evaluated at 3, 6 and 12 months after intensive care unit discharge with assessment of physical, mental and cognitive impairments. Critical illness polyneuromyopathy was diagnosed in 23 patients (39%). Handgrip dynamometry was 70% predicted at 3 months and significantly improved over time, whereas the 6 min walk test (80% predicted) and severe fatigue (27% of patients) did not. Independence in activities of daily living (ADL) was achieved by 98% at 3 months. Cognitive impairment (28% at 3 months) improved over time, whereas depression, anxiety and post-traumatic stress disorder symptoms, present in 9%, 10% and 4% at 3 months, did not. Normalised health-related quality of life was good. COVID-19-associated ARDS leads to persisting impairment in performance-based measures of physical function, while ADL, cognitive and mental health status, and health-related quality of life may be less impaired. Trial registration number NCT04608994 .